News of Organizations and Institutions (Academy of Management Journal, 1962)
Presents updates on organizations and institutions as of December 1962. Leaders of major business organizations that have accepted the invitation of David Rockefeller to serve on the advisory board of the 13th International Management Congress; Establishment of a School of Commerce at Kansas State University in Manhattan in July 1962; Changes in management, purpose and objectives of the Association of Consulting Management Engineers.